Plasmid-Mediated Quinolone Resistance: a Multifaceted Threat - Strahilevitz, Jacob; Jacoby, George A.; Hooper, David C.; Robicsek, Ari (Clinical Microbiology Reviews, 2009)
Classifications Services CMR Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CMR About CMR Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CMR RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0893-8512 Online ISSN: 1098-6618 Copyright © 2014 by the American Society for Microbiology. For an alternate route to CMR .asm.org, visit: CMR